Measurement of the energy dependence of the total photon-proton cross section at HERA - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Antonelli, S; Antonioli, P; Antonov, A; Arneodo, M; Aushev, V; Aushev, Y; Bachynska, O; et al. (2011)
The energy dependence of the photon-proton total cross section, σtotγp, was determined from e+p scattering data collected with the ZEUS detector at HERA at three values of the center-of-mass energy, W, of the γp system in the range 194